2022
DOI: 10.3389/fphar.2022.1027731
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rc, as an FXR activator, alleviates acetaminophen-induced hepatotoxicity via relieving inflammation and oxidative stress

Abstract: Acetaminophen (APAP) intake leads to excessive NAPQI deposition, stimulating inflammatory and oxidative stress and causing fatal liver injury. However, the detailed molecular mechanism involved is unknown, and effective therapeutic approaches remain insufficient. In this study, we discovered that treatment with ginsenoside Rc can prevent the inflammatory response caused by APAP and oxidative stress in mouse primary hepatocytes (MPHs), along with the corresponding changes in related genes. Additionally, Ginseno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Liu et al found that kaempferol-7-O-rhamnoside could bind to FXR and upregulate FXR gene expression to increase cell viability, enhance liver function, and ameliorate oxidative stress in APAP-treated human L02 hepatocytes [121]. Zhong et al reported that ginsenoside Rc could alleviate APAP-induced hepatotoxicity, inflammation, oxidative stress, and apoptosis by upregulating FXR expression in mice and mouse primary hepatocytes [122].…”
Section: Ba and Fxr Agonistsmentioning
confidence: 99%
“…Liu et al found that kaempferol-7-O-rhamnoside could bind to FXR and upregulate FXR gene expression to increase cell viability, enhance liver function, and ameliorate oxidative stress in APAP-treated human L02 hepatocytes [121]. Zhong et al reported that ginsenoside Rc could alleviate APAP-induced hepatotoxicity, inflammation, oxidative stress, and apoptosis by upregulating FXR expression in mice and mouse primary hepatocytes [122].…”
Section: Ba and Fxr Agonistsmentioning
confidence: 99%
“…GRc has been reported to enhance bone development in ovariectomy-induced osteoporotic mice and to stimulate osteogenic differentiation in vitro through the Wnt/β-catenin signaling pathway [64]. Additionally, an in vivo study demonstrated that GRc administration significantly attenuated acetaminophen-induced hepatotoxicity, repaired liver damage, and improved survival [65]. In addition, in a dose-dependent manner, GRc reduced the proliferation and viability of 3T3L1 preadipocytes, adipocyte numbers, and lipid accumulation in maturing 3T3L1 preadipocytes, indicating it inhibited lipogenesis [66].…”
Section: Ginsenoside Rc (Grc)mentioning
confidence: 99%